A Milestone in Global Recent Push for Environmental Protection and the Japanese Experience of the “Big Four” Pollution Diseases through the Lens of International Aid - Oscar A. Gómez Salgado (Budapest International Research and Critics University, 2020)
This paper explains a brief examination of a milestone in global recent push for environmental protection, the world-renown ‘four’ big pollution diseases of Japan, and their use inside country’s development assistance. This branch of foreign policy was selected because of its exceptional potential to disseminate country’s voice, ideal niche for experience to be heralded, and opportunity to actually prevent similar catastrophes in other countries, thanks to its access to resources and political leverage. Experience is an overtly accepted source of lessons but, as a social phenomenon, it is not static. This essay is an examination of the use of the ‘four’ big pollution diseases experience inside Japanese initiatives on international aid, looking for the changes in understanding such tragic events. Attention is placed on the elements introduced and the nuances of meaning among them. The period reviewed, from the late 80’s to 2005, indicates a positive movement of the official view towards a comprehensive recognition of the history, not without voids and pending challenges.